2023
DOI: 10.1002/fsn3.3288
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the stability and bioavailability of pumpkin lutein using β‐cyclodextrin microcapsules

Abstract: Growing concerns about food nutrition and food supplies have encouraged the development of effective constituents. Lutein is an important nutrient element, and its health benefits are gradually being recognized. Lutein, as a carotenoid antioxidant, can protect cells and organs from damage caused by free radicals. However, in processing, storage, and usage, lutein is unstable and often undergoes isomerization and oxidative decomposition, which limits its wide range of applications. β‐Cyclodextrin is an ideal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Lastly, the solution is filtered and dried to include complex powder [18,40]. To mention some studies with this methodology, we can highlight the preparation of a container based on lutein and β-CD with possible applications as IP or AP [67].…”
Section: Precipitation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the solution is filtered and dried to include complex powder [18,40]. To mention some studies with this methodology, we can highlight the preparation of a container based on lutein and β-CD with possible applications as IP or AP [67].…”
Section: Precipitation Methodsmentioning
confidence: 99%
“…With the help of CDs, this damage can be slowed down, encasing it in its interior cavity. In another study, a possible application of an AP based on β-CD and lutein was performed, where the encapsulated lutein was guaranteed to protect its antioxidant properties [67]. Other plant pigments, like carotenoids, are flavonoids with antioxidant activity.…”
Section: Active Packagingmentioning
confidence: 99%
“…Therefore, technical advances on microencapsulation are being developed to solve these problems. 122 However, clinical studies on age-related macular degeneration (AMD) recommend that the consumption of food-based lutein is the best option, as the administration of supplements for AMD have given contradictory results. 123 This may be because high-dose administration of a single xanthophyl-carotenoid like lutein has the effect of altering the plasma and other tissue concentrations of other xanthophylls such as zeaxanthin, and carotenoids such as β-carotene, which are also beneficial for the prevention of human disease.…”
Section: Abnormal Levels Of No May Contribute To Cardiovascular and B...mentioning
confidence: 99%
“…Regarding the food matrix and other dietary components that affect its stability, 122 the Lakshminarayana and colleagues animal study has found that olive oil (OO) is the optimum "carrier source" to achieve the best postprandial plasma concentrations of lutein that can reach the eyes. 24 In this study, the absorption of lutein did not affect the content of other carotenoids in animals.…”
Section: Abnormal Levels Of No May Contribute To Cardiovascular and B...mentioning
confidence: 99%
“…The food processing (heat, pH etc) that degrades the structural stability of lutein makes its bioavailability even worse. Therefore, technical advances on microencapsulation are being developed to solve these problems [122]. However, clinical studies on age-related macular degeneration (AMD) recommend that the consumption of food-based lutein is the best option, as the administration of supplements for AMD have given contradictory results [123].…”
Section: Why Lutein-rich Food Can Be An Ideal Supplementmentioning
confidence: 99%